The Use of Counting Media Sticks on Addition Materials to Improve Grade 1 Students’ Learning Outcomes - Siti Masrukahtin; M. Bambang Edi Siswanto (IJPSE : Indonesian Journal of Primary Science Education, 2022)
Schools with backgrounds that do not meet the learning media will have an effect on the quality of students' learning. In addition, as a teacher must also be able to motivate and provide a pleasant learning experience. This research was conducted using a counting stick learning medium in 1st grade math subjects with summation materials in the hope that students can improve learning outcomes. This research process uses a causative approach with a type of pre-esperimental design (nondesign) one-group pretest-posttest. This form of research compares the results of pretest and posttest with given a treatment. Data is obtained from the results of pre-test and post-test as well as the student response questionnaire to the use of media stick count. The results of the study from the influence of media sticks calculate the summation material on student learning outcomes before being given and after the provision of learning using media stick count on the summation material is still below the average Minimum Provision Criteria (KKM) which is 75. Compared to after being given steamy treatment of learning using a media stick count, the results showed a significant level of student learning outcomes that can be seen from post-test scores with an average score of 91.